Bahiagrass for Florida Lawns - Laurie E. Trenholm; John L. Cisar; J. Bryan Unruh (EDIS, 2011)
Bahiagrass is a popular, low-maintenance lawn grass that does well with limited water and fertilizer inputs. Although bahiagrass does not produce a carpet-like, dense lawn like some other warm-season lawn grasses, it does provide a good, low-maintenance lawn where slightly reduced visual quality is acceptable. This revised 6-page fact sheet was written by L. E. Trenholm, J. L. Cisar, and J. B. Unruh and published by the UF Department of Environmental Horticulture, April 2011.